Protein composition of silk filaments spun under water by caddisfly larvae - Yonemura, Naoyuki; Sehnal, Frantisek; Mita, Kazuei; Tamura, Toshiki (Biomacromolecules, 2006)
Silk fiber produced by the larvae of Trichoptera (caddisflies) and Lepidoptera (moths and butterflies) is composed of two filaments embedded in a layer of glue proteins. In an aerial environment Lepidoptera spin silk filaments assembled from heavy chain fibroin (H-fibroin), light chain fibroin (L-fibroin), and the glycoprotein P25. The silk filament of caddisflies, which is produced and persists in water, contained homologues of H-fibroin (>500 kDa) and L-fibroin (25 kDa) but not of P25. The amphiphilic nature of H-fibroin and its high content of charged amino acids probably facilitate the secretion and storage of a covalently linked L-fibroin/H-fibroin dimer in the absence of P25. Several types of short amino acid motifs were arranged in orderly fashion in the regularly reiterated repeats that made up more than 95% of the length of H-fibroin. The H-fibroins of Hydropsyche angustipennis and Limnephilus decipiens from different caddisfly suborders contained GPXGX, SXSXSXSX, and GGX motifs such as the lepidopteran and spider silks but differed from them by a lack of poly(A) and poly(GA) motifs. H-fibroins of both caddisfly species harbored a conserved repeat of 31 residues but were distinguished by a few species-specific motifs and their organization in higher order repeats. Structural differences may be related to the silk function as a catching net in H. angustipennis and a stitching fiber in L. decipiens.
Keywords: sekvenční seřazení; sekvence nukleotidů; hmyz; sekvenční homologie aminokyselin; hedvábí; Sequence Homology, Amino Acid; regulace genové exprese; larva; Molecular Sequence Data; sekvenční homologie nukleových kyselin; fibroiny; molekulární sekvence - údaje; Fibroins; konzervovaná sekvence; DNA, Complementary; Silk; komplementární DNA; zvířata; Insecta; Amino Acid Sequence; Conserved Sequence; Gene Expression Regulation; Base Sequence; Sequence Homology, Nucleic Acid; Sequence Alignment; Lepidoptera; Larva; Animals; sekvence aminokyselin